تطور اساليب اللعب في كرة الطائرة - دراسة تاريخية وتكتيكية - الوحيدي محمد/يحي احمد قنديل (Institut d’Éducation Physique et Sportive / UNIVERSITY OF MOSTAGANEM, 2025)
تتمثل مشكلة الدراسة في "كيف تطورت أساليب اللعب في كرة الطائرة على مر العصور؟" وتهدف الدراسة إلى تحليل تطور أساليب اللعب في كرة الطائرة تاريخيًا وتكتيكيًا، والتعرف على تأثير تلك التطورات على الأداء الرياضي للاعبين. كما تسعى الدراسة لإبراز الدور الكبير الذي تلعبه هذه الأساليب في تحسين الأداء الفني والتكتيكي للاعبين، وتحديد العوامل التي ساهمت في هذا التطور عبر العصور. تم وضع فرضيتين رئيسيتين هما: "أساليب اللعب في كرة الطائرة تطورت بشكل ملحوظ مع مرور الوقت، ما أثر بشكل إيجابي على أداء اللاعبين" و"التكتيك الحديث في كرة الطائرة هو نتاج التطور المستمر للأساليب عبر تاريخ اللعبة". اعتمد الباحث في منهج البحث على المنهج التاريخي والتحليلي وذلك لدراسة تطور اللعبة وأثرها عبر الزمن. تم جمع البيانات من خلال مراجعة الأدبيات والمصادر التاريخية المتعلقة باللعبة، بالإضافة إلى إجراء مقابلات مع بعض الخبراء والمدربين في هذا المجال. توصل الباحث إلى أن الأساليب التكتيكية والتقنية في كرة الطائرة قد شهدت تطورًا كبيرًا، وأن هذا التطور أثر بشكل إيجابي في رفع مستوى الأداء. كما أوصى الباحثان بضرورة الاستمرار في دراسة التطورات التكتيكية لتحديث الاستراتيجيات التدريبية وتعزيز مستوى اللعبة على الصعيدين المحلي والدولي./ // // // // // // / The problem of the study is "How have volleyball playing styles evolved over time?" The study aims to analyze the historical and tactical development of volleyball playing styles, identifying how these developments have influenced athletes' performance. The study also seeks to highlight the significant role these styles play in improving players' technical and tactical performance, and determine the factors that contributed to this evolution over the centuries. Two main hypotheses were set: "Volleyball playing styles have evolved significantly over time, which positively impacted players' performance" and "Modern tactics in volleyball are the result of continuous evolution of playing styles throughout the game's history." The researcher used a historical and analytical approach to study the development and impact of the game over time. Data was gathered by reviewing literature and historical sources related to the game, in addition to conducting interviews with experts and coaches in the field. The researcher concluded that both tactical and technical styles in volleyball have significantly evolved, and this evolution positively influenced performance. The researcher recommended the continuous study of tactical developments to update training strategies and enhance the game’s level both locally and internationally.
LES-2025-39
Keywords: كرة الطائرة; - أساليب اللعب; - التكتيك الرياضي; - تطور الأداء; تاريخ كرة الطائرة; Volleyball; - Playing styles; Sports tactics; History of volleyball; Performance development